The perceived effects of student employment on the academic performance of selected UP Diliman students - David, Maureen Pilo; Gabriel, Florenda S. (2008)
The study was conducted to determine the perceived effects of student employment on the academic performance of selected students of UP Diliman. A semi-structured interview was conducted among twenty (20) purposively selected working students of UP Diliman. The study employed content analysis in which information gathered were working in various jobs which provided flexible working hours compatible to their working hours compatible to their class schedules such as jobs in call centers and tutorial centers. Economic reasons were the primary factor which influenced students to enter the labor force. Economic reasons were the primary factor which influenced students to enter the labor force. Majority of them were working to alleviate the financial burden of their college education while some respondents were working to provide for the basic needs of the family. Other respondents were working for personal growth such as to gain work experience and be productive, responsible and mature individuals. The negative effects of student employment on the academic performance were frequent class absences and tardiness, no available time for library research and late submission of school papers and projects. Positive impacts of student employment were financial gains, development of self-management skills (time management, financial management and organization), personal growth (maturity, responsibility, discipline, positive outlook in life and professionalism) and work experience.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Part-time students -- Philippines